Origin and Biogeography of the Colourful Sap‐Sucking Sea Slugs Genus Thuridilla Bergh, 1872 (Mollusca, Gastropoda, Heterobranchia) - M. Rosario Martín‐Hervás; Leila Carmona; Patrick J. Krug; Terence Gosliner; J. Lucas Cervera; Manuel António E. Malaquias (Journal of Biogeography, 2025)
Aim Thuridilla Bergh, 1872, is a lineage of herbivorous sea slugs externally distinguished by bright colours and distinctive patterns of lines and spots. Recent work revealed an exceptionally rapid, cryptic radiation of 13 species in the Indo‐Pacific, raising questions about mechanisms of speciation in this group. Here, we (i) study the diversification and historical biogeography of Thuridilla in a phylogenetic context and (ii) assess the role of dispersal and vicariance as the predominant mode of speciation in the genus. Location Tropical and temperate regions of the Atlantic and Indo‐Pacific. Major Taxa Studies Gastropoda, Sacoglossa. Methods A nearly complete taxon set with 28 out of 32 recognised species of Thuridilla was used, in a total sample of 172 specimens, together with sacoglossan outgroups. Phylogenetic relationships were determined using a multi‐locus approach combining two mitochondrial (COI and 16S) and one nuclear gene (H3). Species relationships, diversification times, and ancestral geographical ranges were inferred using relaxed‐clock methods together with Bayesian discrete phylogeographic methods under three calibration scenarios using the oldest known fossil of Sacoglossa, Berthelinia elegans Crosse, 1875, and tectonic events. Results Thuridilla species branched off into four major clades in all calibration scenarios: two groups from the Atlantic plus Indo‐West Pacific (5 and 6 species) and two clades from the Indo‐West Pacific (4 and 17 species). The highest diversity of the genus is in the Western Pacific (14 spp.) with a peak in the East Indies Triangle (18 spp.), whereas the Atlantic is depauperate with only four species occurring in this ocean basin. Divergence between Atlantic and Indo‐West Pacific lineages occurred in two main temporal periods: the Miocene and the Pliocene. Speciation events within the 13 cryptic species‐complex fell mostly within Plio‐Pleistocene times. Main Conclusions The best supported hypothesis was an Indo‐West Pacific origin of Thuridilla between 28 and 18 Mya during the Early Miocene. In the western Pacific, speciation likely occurred during transient allopatry during Plio‐Pleistocene sea‐level fluctuations. Under the three tested calibration scenarios, the limited diversity of the Atlantic Ocean is hypothesized to be derived from Miocene vicariant events associated with the closure of the Tethys Sea, dispersal across southern Africa, or long‐distance dispersal across the East Pacific Barrier prior to the uplift of the Isthmus of Panama. Thuridilla is absent in the Eastern Pacific, potentially resulting from the extinction of ancestral lineages following the uplift of the Isthmus of Panama. Near‐complete sampling of diversity and reconstruction of historical biogeography thus yielded new insight into the relative contributions of dispersal versus vicariance during speciation over the history of this widely distributed, colourful genus.

The Heterobranchia gastropods from the Cabo Verde Islands (NE Atlantic): A hot-spot of endemism - Manuel António E. Malaquias; Martina Turani; Evandro Lopes; Juan L. Cervera (Regional Studies in Marine Science, 2025)

CLIMF2: A climatological model of the ionospheric F2 layer. Part 1: Model methodology - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

CLIMF2: A climatological model of the ionospheric F2 layer. Part 2: Validation and comparison with IRI - Danielle J. Edwards; Thomas E. Chambers; Manuel A. Cervera (Advances in Space Research, 2025)

An intelligent mushroom strain selection model based on their quality characteristics - Jorge Cervera-Gascó; José E. Pardo; Manuel Álvarez-Ortí; Eulogio López-Mata; Diego Cunha Zied; Arturo Pardo-Giménez (Food Bioscience, 2023)

Farming Sparus aurata (Teleostei: Sparidae) in marsh ponds: trophic characterization and trace metal accumulation - J.M. Guerra-García; S. Calero-Cano; I. Donázar-Aramendía; Giráldez I; Morales E; P. Arechavala-Lopez; J.L. Cervera-Currado (Marine Environmental Research, 2023)

Development of the POLIVAR model using neural networks as a tool to predict and identify monovarietal olive oils - Jorge Cervera-Gascó; Adrián Rabadán; Eulogio López-Mata; Manuel Álvarez-Ortí; José E. Pardo (Food Control, 2023)

Properties of the epileptiform activity in the cingulate cortex of a mouse model of LIS1 dysfunction - E. Domínguez-Sala; A. Andreu-Cervera; P. Martín-Climent; R. Murcia-Ramón; S. Martínez; Emilio Geijo-Barrientos (Brain Structure and Function, 2022)
Dysfunction of the LIS1 gene causes lissencephaly, a drastic neurological disorder characterized by a deep disruption of the cortical structure. We aim to uncover alterations of the cortical neuronal networks related with the propagation of epileptiform activity in the Lis1/sLis1 mouse, a model lacking the LisH domain in heterozygosis. We did extracellular field-potential and intracellular recordings in brain slices of the anterior cingulate cortex (ACC) or the retrosplenial cortex (RSC) to study epileptiform activity evoked in the presence of bicuculline (10 µM), a blocker of GABA A receptors. The sensitivity to bicuculline of the generation of epileptiform discharges was similar in wild type (WT) and Lis1/sLis1 cortex (EC 50 1.99 and 2.24 µM, respectively). In the Lis1/sLis1 cortex, we observed a decreased frequency of the oscillatory post-discharges of the epileptiform events; also, the propagation of epileptiform events along layer 2/3 was slower in the Lis1/sLis1 cortex (WT 47.69 ± 2.16 mm/s, n = 25; Lis1/sLis1 37.34 ± 2.43 mm/s, n = 15; p = 0.004). The intrinsic electrophysiological properties of layer 2/3 pyramidal neurons were similar in WT and Lis1/sLis1 cortex, but the frequency of the spontaneous EPSCs was lower and their peak amplitude higher in Lis1/sLis1 pyramidal neurons. Finally, the propagation of epileptiform activity was differently affected by AMPA receptor blockers: CNQX had a larger effect in both ACC and RSC while GYKI53655 had a larger effect only in the ACC in the WT and Lis1/sLis1 cortex. All these changes indicate that the dysfunction of the LIS1 gene causes abnormalities in the properties of epileptiform discharges and in their propagation along the layer 2/3 in the anterior cingulate cortex and in the restrosplenial cortex.

Starting the stowaway pathway: the role of dispersal behavior in the invasion success of low-mobile marine species - M. Ros; C. Navarro-Barranco; M. González-Sánchez; E. Ostalé-Valriberas; L. Cervera-Currado; J. M. Guerra-García (Biological Invasions, 2020)

Soft selective sweeps in fungicide resistance evolution: recurrent mutations without fitness costs in grapevine downy mildew - Chloé E. L. Delmas; Yann Dussert; Laurent Delière; Carole Couture; Isabelle D. Mazet; Sylvie Richart Cervera; François Delmotte (Molecular Ecology, 2017)
Adaptation produces hard or soft selective sweeps depending on the supply of adaptive genetic polymorphism. The evolution of pesticide resistance in parasites is a striking example of rapid adaptation that can shed light on selection processes. Plasmopara viticola , which causes grapevine downy mildew, forms large populations, in which resistance has rapidly evolved due to excessive fungicide use. We investigated the pathways by which fungicide resistance has evolved in this plant pathogen, to determine whether hard or soft selective sweeps were involved. An analysis of nucleotide polymorphism in 108 field isolates from the Bordeaux region revealed recurrent mutations of cytb and CesA3 conferring resistance to quinone outside inhibiting (QoI) and carboxylic acid amide ( CAA ) fungicides, respectively. Higher levels of genetic differentiation were observed for nucleotide positions involved in resistance than for neutral microsatellites, consistent with local adaptation of the pathogen to fungicide treatments. No hitchhiking was found between selected sites and neighbouring polymorphisms in cytb and CesA3 , confirming multiple origins of resistance alleles. We assessed resistance costs, by evaluating the fitness of the 108 isolates through measurements of multiple quantitative pathogenicity traits under controlled conditions. No significant differences were found between sensitive and resistant isolates, suggesting that fitness costs may be absent or negligible. Our results indicate that the rapid evolution of fungicide resistance in P. viticola has involved a soft sweep.

Selection of haploid cell lines from megagametophyte cultures of maritime pine as a DNA source for massive sequencing of the species - I. Arrillaga; M. A. Guevara; J. Muñoz-Bertomeu; D. Lázaro-Gimeno; E. Sáez-Laguna; L. M. Díaz; L. Torralba; I. Mendoza-Poudereux; J. Segura; M. T. Cervera (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The Systemic Absorption of Etoposide after Intravaginal Administration in Patients with Cervical Intraepithelial Lesions Associated with Human Papillomavirus Infection - P. García-López; M. Coll; E. Cervera; L. Reyes-Vermot; M. A. Torres; G. Ábrego-Pérez; A. I. Hernández-Pájaro; G. Castañeda-Hernandez; A. Mohar-Betancourt; A. Meneses (Pharmaceutical Research, 2006)

A genetic map of Maritime pine based on AFLP, RAPD and protein markers - P. Costa; D. Pot; C. Dubos; J. M. Frigerio; C. Pionneau; C. Bodenes; E. Bertocchi; M. -T. Cervera; D. L. Remington; C. Plomion (Theoretical and Applied Genetics, 2000)